Experiences of Burnout, Self-Care, and Recovery of Female University Counsellors in Taiwan - Lin, Yii-Nii (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to describe the burnout, self-care, and recovery experiences of female university counsellors working at a university counselling centre in Taiwan. The 9 participants had an average age of 42.44 years and had worked at the centre for an average of 11.3 years. A qualitative method of phenomenology with in-depth interviews was adopted. Themes that emerged from the data analysis included (a) burnout is influenced by conflicts between work environment and family; (b) burnout is influenced by changes on campus and in the counselling profession; (c) self-awareness, self-assessment, and action are keys to self-care; and (d) recovery requires the right balance between self, life, and work.